Linking Government Data - Wood, David; SpringerLink (Online service). (New York, NY Springer, 2011)
Linking Government Data provides a practical approach to addressing common information management issues. The approaches taken are based on international standards of the World Wide Web Consortium. Linking Government Data gives both the costs and benefits of using linked data techniques with government data; describes how agencies can fulfill their missions with less cost; and recommends how intra-agency culture must change to allow public presentation of linked data. Case studies from early adopters of linked data approaches in international governments are presented in the last section of the book. Linking Government Data is designed as a professional book for those working in Semantic Web research and standards development, and for early adopters of Semantic Web standards and techniques. Enterprise architects, project managers and application developers in commercial, not-for-profit and government organizations concerned with scalability, flexibility and robustness of information management systems will also find this book valuable. Students focused on computer science and business management will also find value in this book.
Part I Publishing Linked Government Data -- 1 The Joy of Data - A Cookbook for Publishing Linked Government Data on the Web -- 2 Methodological Guidelines for Publishing Government Linked Data -- 3 Producing and Using Linked Open Government Data in the TWC LOGD Portal -- 4 Linking Geographical Data for Government and Consumer Applications -- Part II Improving Linked Data Quality -- 5 Creating and Publishing Semantic Metadata about Linked and Open Datasets -- 6 StdTrip: Promoting the Reuse of Standard Vocabularies in Open Government Data -- 7 Official Statistics and the Practice of Data Fidelity -- Part III Consuming Linked Government Data -- 8 Visualizing Open Government: Case Study of the Canadian Recordkeeping Approach -- 9 Linking Australian Government Data for Sustainability Science : A Case Study -- 10 The Web is My Back-end: Creating Mashups with Linked Open Government Data -- Glossary -- Index.
Keywords: Electronic government information; Semantic Web; Linkers (Computer programs).; Electronic books